2020
DOI: 10.3390/d12090329
|View full text |Cite
|
Sign up to set email alerts
|

Water Mite Diversity (Acariformes: Prostigmata: Parasitengonina: Hydrachnidiae) from Karst Ecosystems in Southern of Mexico: A Barcoding Approach

Abstract: Water mites represent the most diverse and abundant group of Arachnida in freshwater ecosystems, with about 6000 species described; however, it is estimated that this number represents only 30% of the total expected species. Despite having strong biotic interactions with their community and having the potential to be exceptional bioindicators, they are frequently excluded from studies of water quality or ecology, due to actual and perceived difficulties of taxonomic identification in this group. The objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…Though several BIN's are shared among all systems, the Sørensen analysis shows that each system has a unique assemblage of species. This singularity for each aquatic system makes evident the fragility of these ecosystems in the whole region and confirms previous analyses with mites [40]. We do not know why each system has a unique assemblage of species if they eventually can be connected in the surface after floods or through the complex underground system of rivers.…”
Section: Species Composition Comparisonsupporting
confidence: 81%
See 2 more Smart Citations
“…Though several BIN's are shared among all systems, the Sørensen analysis shows that each system has a unique assemblage of species. This singularity for each aquatic system makes evident the fragility of these ecosystems in the whole region and confirms previous analyses with mites [40]. We do not know why each system has a unique assemblage of species if they eventually can be connected in the surface after floods or through the complex underground system of rivers.…”
Section: Species Composition Comparisonsupporting
confidence: 81%
“…The high diversity of mites in this region was noticed in two previous studies [16,40]. Their relevance as indicators of water quality is well known [41].…”
Section: Dna Barcoding Baselinementioning
confidence: 58%
See 1 more Smart Citation
“…The application of DNA barcoding to species discovery and identification is wellestablished, including the ability of the methodology to cope with different life stages and provide insights into cryptic species diversity [39]. Since these initial applications, rapid species identification with DNA barcodes has been deployed in several fields, including forensic science [40], control of the food supply chain [6], and understanding disease [41].…”
Section: Dna Barcoding Enhances Biodiversity Discovery and Monitoringmentioning
confidence: 99%
“…Public databases, including the Barcode of Life Database (www.boldsystems.org) or GenBank (www.ncbi.nlm.nih.gov), as well as the use of new bioinformatic tools, represent a breakthrough in species identification. This line of research is represented by the studies of Montes-Ortiz and Elías-Gutiérrez [9], who investigated water mites in the Yucatan Peninsula of Mexico. Applying the above-mentioned method, these authors identified 77 genetic groups or putative species corresponding to 18 genera.…”
mentioning
confidence: 99%